Aspects of structure-activity relationships and physiology of gastrin and related peptides - Napier, Beverley Jean (Department of Medicine, 2020)
When, in 1973, I embarked upon this study, the hormone gastrin seemed a suitable hormone to study with regard to investigation of structure-activity relationships and physiology of a peptide hormone. Gastrin was best known at that stage as a linear peptide comprising 17 amino acids, which was stable at room temperature and was resistant to degradation by vigorous treatments such as boiling {Gregory and Tracy, 1964; Berson and Yalow, 1971; Yalow and Berson, 1972) and pH extremes (Piszkiewicz, 1974). Such a molecule could thus be studied at room temperature, using conventional biochemical techniques, without the need for any special precautions to preserve its integrity.